THE SYNERGISTIC POTENTIAL OF THE DEPARTMENT OF SOCIOLOGY AND PSYCHOLOGY MANAGEMENT - Y. Krasovsky (Вестник университета)
The paper first analyzes the synergistic potential of the department of sociology and psychology of management, which is determined by the status of its three-pronged; It offers a brief interpretation of the resource criteria, whose development and reveals the originality of the aggregate of the cathedral building. Article - principally new development based on a rethinking of previous publications of the author.